PENGARUH PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR PENGETAHUAN BAHASA INDONESIA (KETERAMPILAN MENULIS) TEMA CITA-CITAKU PADA SISWA KELAS IV SD GUGUS LETKOL WISNU DITINJAU DARI CARA GURU BERTANYA - ., Ni Made Dwi Pradnyawati; ., Dr. M.G. Rini Kristiantari,M.Pd; ., Dra. Ni Nyoman Ganing, M.Hum (MIMBAR PGSD Undiksha, 2015)
Penelitian ini bertujuan untuk mengetahui perbedaan yang signifikan hasil belajar pengetahuan Bahasa Indonesia (keterampilan menulis) tema cita-citaku antara siswa yang dibelajarkan melalui pendekatan saintifik berbasis pertanyaan langsung dan siswa yang dibelajarkan dengan pendekatan saintifik berbasis pertanyaan tidak langsung pada siswa kelas IV SD Gugus Letkol Wisnu. Penelitian ini merupakan penelitian pra-eksperimen dengan rancangan penelitian yang digunakan adalah The Static Group Pretest-Posttest Design. Populasi dalam penelitian ini adalah semua kelas IV SD Gugus Letkol Wisnu, meliputi 7 SD berjumlah 350 siswa. Pengambilan sampel dengan teknik random sampling dan diperoleh kelas IVa SD Negeri 1 Peguyangan berjumlah 41 siswa sebagai kelas terteliti dengan tindakan berupa pertanyaan langsung dan kelas IVa SD Negeri 5 Peguyangan berjumlah 38 siswa sebagai kelas terteliti dengan tindakan berupa pertanyaan tidak langsung. Data yang dikumpulkan adalah hasil belajar pengetahuan Bahasa Indonesia (keterampilan menulis) berupa nilai kognitif. Nilai kognitif dikumpulkan menggunakan tes hasil belajar dalam bentuk tes pilihan ganda biasa. Data dianalisis dengan uji-t. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan hasil belajar pengetahuan Bahasa Indonesia (keterampilan menulis) tema cita-citaku antara siswa yang dibelajarkan melalui pendekatan saintifik berbasis pertanyaan langsung dan siswa yang dibelajarkan dengan pendekatan saintifik berbasis pertanyaan tidak langsung pada siswa kelas IV SD Gugus Letkol Wisnu dengan thitung=2,47 > ttabel=1,65 pada taraf signifikansi 5%. Berdasarkan kriteria pengujian maka H0 ditolak dan Ha diterima. Dengan demikian dapat disimpulkan bahwa pendekatan saintifik berpengaruh terhadap hasil belajar pengetahuan Bahasa Indonesia (keterampilan menulis) tema cita-citaku pada siswa kelas IV SD Gugus Letkol Wisnu ditinjau dari cara guru bertanya. Kata Kunci : pendekatan saintifik, hasil belajar, pengetahuan Bahasa Indonesia (keterampilan menulis), cara guru bertanya This study aimed to determine the significant differences effect of students’ Indonesian language knowledge (writing skill) which was taught through scientific approach based direct questions with the students that was taught through scientific approach based indirect questions with my aspiration theme on fourth grade students at SD Gugus Letkol Wisnu. This research was type of pre-experimental research which used the group static Pretest-Postest design. The population of this study was all of the fourth grade students at SD gugus Letkol Wisnu which consisted of 350 students in 7 classes. Samples were gained by random sampling technique. The sample for this technique was class IVa SD Negeri 1 Peguyangan as the group which was taught by scientific approach based direct questions. However, class IVa SD Negeri 5 Peguyangan as the group which was taught by scientific approach based indirect questions. The data was collected from the cognitive result from the students in learning Indonesian language (writing skill). The cognitive score was gained by using multiple choices test and analyzed by t-test. This result showed that there was significant different effect of students’ Indonesian language knowledge (writing skill) which was taught through scientific approach based direct questions with the students that was taught through scientific approach based indirect questions with my aspiration theme on fourth grade students at SD Gugus Letkol Wisnu. Based on the t-test results, tobserved = 2,47 > ttable = 1,65 in significant of 5%. Based on this comparison, H0 was rejected and Ha was accepted. Thus, it can be concluded that the scientific approach gave effect on students’ learning outcome in Indonesian language knowledge (writing skill) with my aspiration theme on fourth grade students at SD Gugus Letkol Wisnu based on question type of the teacher.This study aimed to determine the significant differences effect of students’ Indonesian language knowledge (writing skill) which was taught through scientific approach based direct questions with the students that was taught through scientific approach based indirect questions with my aspiration theme on fourth grade students at SD Gugus Letkol Wisnu. This research was type of pre-experimental research which used the group static Pretest-Postest design. The population of this study was all of the fourth grade students at SD gugus Letkol Wisnu which consisted of 350 students in 7 classes. Samples were gained by random sampling technique. The sample for this technique was class IVa SD Negeri 1 Peguyangan as the group which was taught by scientific approach based direct questions. However, class IVa SD Negeri 5 Peguyangan as the group which was taught by scientific approach based indirect questions. The data was collected from the cognitive result from the students in learning Indonesian language (writing skill). The cognitive score was gained by using multiple choices test and analyzed by t-test. This result showed that there was significant different effect of students’ Indonesian language knowledge (writing skill) which was taught through scientific approach based direct questions with the students that was taught through scientific approach based indirect questions with my aspiration theme on fourth grade students at SD Gugus Letkol Wisnu. Based on the t-test results, tobserved = 2,47 > ttable = 1,65 in significant of 5%. Based on this comparison, H0 was rejected and Ha was accepted. Thus, it can be concluded that the scientific approach gave effect on students’ learning outcome in Indonesian language knowledge (writing skill) with my aspiration theme on fourth grade students at SD Gugus Letkol Wisnu based on question type of the teacher.This study aimed to determine the significant differences effect of students’ Indonesian language knowledge (writing skill) which was taught through scientific approach based direct questions with the students that was taught through scientific approach based indirect questions with my aspiration theme on fourth grade students at SD Gugus Letkol Wisnu. This research was type of pre-experimental research which used the group static Pretest-Postest design. The population of this study was all of the fourth grade students at SD gugus Letkol Wisnu which consisted of 350 students in 7 classes. Samples were gained by random sampling technique. The sample for this technique was class IVa SD Negeri 1 Peguyangan as the group which was taught by scientific approach based direct questions. However, class IVa SD Negeri 5 Peguyangan as the group which was taught by scientific approach based indirect questions. The data was collected from the cognitive result from the students in learning Indonesian language (writing skill). The cognitive score was gained by using multiple choices test and analyzed by t-test. This result showed that there was significant different effect of students’ Indonesian language knowledge (writing skill) which was taught through scientific approach based direct questions with the students that was taught through scientific approach based indirect questions with my aspiration theme on fourth grade students at SD Gugus Letkol Wisnu. Based on the t-test results, tobserved = 2,47 > ttable = 1,65 in significant of 5%. Based on this comparison, H0 was rejected and Ha was accepted. Thus, it can be concluded that the scientific approach gave effect on students’ learning outcome in Indonesian language knowledge (writing skill) with my aspiration theme on fourth grade students at SD Gugus Letkol Wisnu based on question type of the teacher.keyword : scientific approach, learning outcomes, Indonesian language knowledge (writing skill) and question types of teacher